(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article scientifically examines the possibilities of using digital technologies and artificial intelligence tools in the translation process. The study highlights the role of machine translation, CAT tools, corpus linguistics, and neural translation systems in modern translation studies. Furthermore, it analyzes the impact of artificial intelligence on translation quality, pragmatic adaptation, and the professional competence of translators.